2013
DOI: 10.1177/2325967113517078
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomic Pattern of Injuries in Acute Inversion Ankle Sprains

Abstract: Background:There are little data on the incidence and patterns of injuries seen on magnetic resonance imaging (MRI) in acute inversion ankle sprains. This study may help in the understanding of the pathomechanics, natural history, and outcomes of this common injury.Study Design:Case series; Level of evidence, 4.Methods:From June 2011 to June 2013, a total of 64 consecutive patients had MRI of the ankle performed for acute inversion injury to the ankle. All injuries/pathologies reported were recorded.Results:On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Eight of the 13 articles described diagnostic imaging findings, with MRI being the modality of focus in all of those articles. 5,6,[8][9][10]15,16,21,25 One study showed that there was increased medial space widening on radiography with external rotation of the ankle while holding the hindfoot in varus. Four articles included a classification scheme for their findings, which are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of the 13 articles described diagnostic imaging findings, with MRI being the modality of focus in all of those articles. 5,6,[8][9][10]15,16,21,25 One study showed that there was increased medial space widening on radiography with external rotation of the ankle while holding the hindfoot in varus. Four articles included a classification scheme for their findings, which are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…14,19,22 The superficial ligament is the primary restraint against rotation, acting to prevent external rotation of the talus. 22 The included studies did not describe any physical examination maneuver that would 13 IV Chun et al, 2015 6 IV Wang et al, 2014 25 IV Jeong et al, 2014 15 IV Crim et al, 2015 8 IV Crim et al, 2011 9 IV Khor et al, 2013 16 IV Roemer et al, 2014 21 III Chhabra et al, 2010 5 IV Femino et al, 2013 10 IV Bucchorn et al, 2011 3 III Lack et al, 2012 17 V test for rotational instability or increased posterior translation. Given the function of the deltoid complex, these would arguably be the most important tests for clinically determining competence of the deltoid ligament.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, there were anterior talofibular ligament (ATFL) injuries in 75% of patients after acute inversion ankle sprain with a combined ATFL and calcaneofibular ligament (CFL) in 41%. 2 In another study, the prevalence of DL injury in patients with chronic lateral ankle instability was 36%. 3 There are no studies to our knowledge investigating injury of the talonavicular ligament (TNL) in patients presenting with an ankle sprain.…”
Section: Introductionmentioning
confidence: 94%
“…Biomechanically, the ATFL is the weakest and most commonly injured of the 3 ligaments, whereas the PTFL is the strongest and is rarely injured except in the setting of ankle dislocation [6‐10]. Additional injuries that may occur with the inversion ankle sprain include the following: bone bruise or fracture (lateral malleolus, medial malleolus, tarsal, and metatarsal bones), deltoid ligament injury, tendon injury, osteochondral lesion, syndesmosis injury, and alterations of the sinus tarsi [11]. Khor et al identified an osteochondral lesion in 6 of 34 patients (18%) with concomitant lateral ligament injury following an inversion ankle sprain [11].…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Additional injuries that may occur with the inversion ankle sprain include the following: bone bruise or fracture (lateral malleolus, medial malleolus, tarsal, and metatarsal bones), deltoid ligament injury, tendon injury, osteochondral lesion, syndesmosis injury, and alterations of the sinus tarsi [11]. Khor et al identified an osteochondral lesion in 6 of 34 patients (18%) with concomitant lateral ligament injury following an inversion ankle sprain [11]. Osteochondral lesions are most common in the talus after an inversion injury, and can accelerate the development of osteoarthritis (Figure 2).…”
Section: Clinical Backgroundmentioning
confidence: 99%